Neuroni specchio o dimensione creativa del vedere? - Fiori Nastro, Federico (Il sogno della farfalla, 2022)
Mirror neurons were first discovered when a group of researchers was studying the activation of different brain areas in macaques in the early 1990s in Parma. The discovery that a group of neurons are activated both when the animal is performing an action and when is observing it represented an unprecedented breakthrough. Shortly after, mirror neurons were identified in the human brain and since then have become a highly discussed and researched topic by the international neuroscientific community. This article analyses the crucial steps that led to the discovery of mirror neurons and their further implications. A theoretical and clinical focus is given to phenomenon such as empathy, children development and the understanding of others’ intentions. Furthermore, psychopathology and psychotherapy are object of further discussion, in the light of the most recent scientific contributions to this topic. In this sense, the human birth theory formulated by the psychiatrist Massimo Fagioli offers a critical perspective on these studies with a specific attention on the development of the newborn in the first year of life.